2009
DOI: 10.1007/s00441-009-0848-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical-stimulation-evoked calcium waves in proliferating and differentiated human keratinocytes

Abstract: Calcium dynamics in the epidermis play a crucial role in barrier homeostasis and keratinocyte differentiation. We have recently suggested that the electro-physiological responses of the keratinocyte represent the frontier of the skin sensory system for environmental stimuli. In the present study, we have evaluated the responses of proliferating and differentiated human keratinocytes to mechanical stress by measuring the intracellular calcium level. Before differentiation, mechanical stress induces a calcium wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
112
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(112 citation statements)
references
References 35 publications
0
112
0
Order By: Relevance
“…It was reported that mechanosensitive ATP release in keratinocytes primarily auto-stimulates P2Y2 receptors and concomitantly triggers Ca 2+ influx through Ca 2+ -permeable channels (Koizumi et al, 2004;Yoshida et al, 2006;Tsutsumi et al, 2009;Boucher et al, 2010;Azorin et al, 2011;Takada et al, 2012;Ho et al, 2013), which then initiates cell migration, the primary process in the wound healing cascade (Dixon et al, 1999;Burrell et al, 2003;Burrell et al, 2005;Braun, et al, 2006;Boucher et al, 2010). We recently suggested that stretch-induced ATP release and a subsequent Ca 2+ increase mediated by P2Y activation (ATP-Ca 2+ signaling) were involved in wound closure in HaCaT keratinocytes (Takada et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that mechanosensitive ATP release in keratinocytes primarily auto-stimulates P2Y2 receptors and concomitantly triggers Ca 2+ influx through Ca 2+ -permeable channels (Koizumi et al, 2004;Yoshida et al, 2006;Tsutsumi et al, 2009;Boucher et al, 2010;Azorin et al, 2011;Takada et al, 2012;Ho et al, 2013), which then initiates cell migration, the primary process in the wound healing cascade (Dixon et al, 1999;Burrell et al, 2003;Burrell et al, 2005;Braun, et al, 2006;Boucher et al, 2010). We recently suggested that stretch-induced ATP release and a subsequent Ca 2+ increase mediated by P2Y activation (ATP-Ca 2+ signaling) were involved in wound closure in HaCaT keratinocytes (Takada et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This augmented Ca 2+ increase in differentiated keratinocytes contributes to the continuous renewal of the cornified layer, which is essential for the epidermal barrier function (Tsutsumi et al, 2009). A steep Ca 2+ gradient exists within the normal mammalian epidermis.…”
Section: Introductionmentioning
confidence: 99%
“…These responses have been shown to play a critical role in long established mechanisms such as action potential generation in electrically excitable cells (1,2) and have been implicated in a wide variety of intracellular signaling and regulatory pathways, including initiation of apoptosis (3), alteration of cell surface protein expression (4), and response to mechanical stress on the plasma membrane (5). The vast majority of changes in intracellular calcium is extremely rapid and occurs within a nanosecond timescale.…”
mentioning
confidence: 99%
“…(16) and (17). Although it is difficult to obtain analytical expression of a n (ρ) for general ρ, the integration can be performed when ρ < 1/2, which yields…”
Section: B the N-link Cyclementioning
confidence: 99%
“…An example is found in calcium propagation in the epidermis [17], where waves of calcium excitation in epidermal cells have a finite propagation range as opposed to normal excitable waves. Also the wave profile is uniform rather than pulselike, which is different from the cases of propagation failure [18,19].…”
Section: Introductionmentioning
confidence: 99%